Decision Support System for Selecting Rescuer Candidates for Basarnas Special Group Using SMART And BORDA - Koto, Muhammad Hendrik; Irawan, Muhammad Dedi (JISA(Jurnal Informatika dan Sains), 2023)
The National Search and Rescue Agency (also known as BASARNAS) is a government agency responsible for offering search and rescue services in the event of an accident or disaster. At BASARNAS there is a special team, the BASARNAS Special Group (BSG). BSG performs rescues during national and international disasters or accidents. BSG itself consists of selected people, namely BSG candidates from all search and rescue office rescuers in Indonesia. BSG candidates themselves are still calculated manually so that it can affect the time efficiency of SAR personnel in making selections, this research was conducted at the Medan Class A Search and Rescue Office. To ensure that BSG candidates are accurate and processed quickly, a decision support system is needed. This time the researchers utilized the Simple Multi Attribute Rating Technique (SMART) and BORDA methods to determine BSG candidates. With the criteria used, namely fitness (K1), physical health (K2), mental health (K3) and creativity (K4). Then the alternatives used are 25 alternatives which include 20 skilled rescuers and 5 beginner rescuers. and the results can be saved in the form of a PDF file. The results of calculations using the SMART and BORDA methods found that among skilled rescuers, Rescuer-T15 is a suitable candidate to become a BSG candidate by obtaining a total score of 6049.25 and among novice rescuers, Rescuer-P5 obtained the highest score of 756.00.